LiSbS2‐mC16: Structure Determination from X‐ray Powder Diffraction Data12. Issue 8 (7th April 2014) - Huber, Sebastian; Pfitzner, Arno
Abstract Monoclinic LiSbS2‐mC16 was synthesized by solid‐state reaction of Li2S, Sb, and S in the ratio 1:2:5 at a temperature of 900 °C. The excess of sulfur serves as a kind of flux and is not incorporated in the structure. The product is air and moisture sensitive. The crystal structure of the dark red product was determined from X‐ray powder diffraction data at 293 K. LiSbS2‐mC16 crystallizes in the space group C2/c (no. 15) with a = 8.0205(8) Å, b = 7.9243(8) Å, c = 6.6987(7) Å, β = 126.303(6)°, V = 343.11(7) Å3, and Z = 4. It forms an ordered NaCl type superstructure, which shows two different sites for the cations, whereas the cubic high temperature modification cF8 exhibits only one position with a mixed occupation by lithium and antimony. Lithium has a slightly distorted octahedral coordination by sulfur. The distortion of the octahedral coordination polyhedron is much stronger in the case of antimony. Therefore it is better described as a 2 + 2 + 2 coordination mode.